2015
DOI: 10.15406/mojor.2015.03.00091
|View full text |Cite
|
Sign up to set email alerts
|

Foot and Ankle Insufficiency Fractures in Rheumatoid Arthritis

Abstract: Abbreviations: RA, rheumatoid arthritis; MRI, magnetic resonance imaging; CT, computerised tomography; XR, X-ray; PTH, parathyroid hormone; DEXA, dual energy X-Ray absorptiometry; NOF, neck of femur; L2-L4, second to fourth lumbar vertebrae; A&E, accident and emergency department; MTP, meta tarso phalangeal Abstract Objectives: To evaluate causes of foot and ankle insufficiency fractures in patients with rheumatoid arthritis. To conduct a literature review of low dose methotrexate induced osteopathy.Case serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Another study reported that the combined use of MTX and GC may have a greater effect on stress fractures than the individual use of each drug [13]. Thirdly, the chronic inflammation and changes in bone structure, including osteopenia, may lead to bone erosion that are associated with RA, causing stress on the bones and contributing to fractures [14]. Finally, the postmenopausal state is also related to bone loss [15].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the combined use of MTX and GC may have a greater effect on stress fractures than the individual use of each drug [13]. Thirdly, the chronic inflammation and changes in bone structure, including osteopenia, may lead to bone erosion that are associated with RA, causing stress on the bones and contributing to fractures [14]. Finally, the postmenopausal state is also related to bone loss [15].…”
Section: Discussionmentioning
confidence: 99%
“…Trickey et al in their case series of three patients with rheumatoid arthritis who presented with acute swollen ankle joints have reported that the diagnosis would be mistaken for an acute flare up of the arthritis, thereby delaying the diagnosis of insufficiency fractures. They concluded that a high index of suspicion was needed in spite of normal plain radiographs to diagnose insufficiency fractures in rheumatoid arthritis patients 5 . Our patient has been taking Methotrexate for 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…Common sites for stress fractures including those seen in RA patients are the weight-bearing bones such as the tibia, metatarsals, calcaneum, femur and pubic ramus. 1,2,4,5 Although the distal radius is a common site for fragility fractures in osteoporotic patients, in a medical literature search we could not find any previously reported case of bilateral radial stress fractures in RA. Stress fractures in our patient were likely a result of repeated mechanical stress due to the use of for support while getting up owing to proximal muscle weakness.…”
mentioning
confidence: 84%
“…3,4 The mechanisms by which RA predisposes to stress fractures include a higher incidence of osteoporosis, poor bone health due to RA itself and the use of corticosteroids. 4,5 Corticosteroids may alter the bone architecture or modelling in addition to the well-known effects on bone mineral density (BMD), leading to the increased risk of fracture. 4 The increased risk persists even after stopping the steroids, particularly if higher doses have been used.…”
mentioning
confidence: 99%
See 1 more Smart Citation